2007
DOI: 10.1002/mnfr.200700086
|View full text |Cite
|
Sign up to set email alerts
|

Common tea formulations modulate in vitro digestive recovery of green tea catechins

Abstract: Epidemiological evidence suggests a role for tea catechins in reduction of chronic disease risk. However, stability of catechins under digestive conditions is poorly understood. The objective of this study was to characterize the effect of common food additives on digestive recovery of tea catechins. Green tea water extracts were formulated in beverages providing 4.5, 18, 23, and 3.5 mg per 100 mL epicatechin (EC), epigallocatechin (EGC), epigallocatechin-gallate (EGCG), and epicatechin-gallate (ECG), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 48 publications
17
172
5
1
Order By: Relevance
“…The low absorption of some fractions may be partly explained by the instability of the compounds during the digestive process. Green et al 32 demonstrated using an in vitro model that 80% of catechins are destroyed during the process of digestion. Studies of anthocyanin pharmacokinetics in humans 33 from either wine or grape juice showed similar T max (0.5-1.5 hours) to fractions IV and V but had a lower serum percentage dose=mL at C max .…”
Section: Discussionmentioning
confidence: 99%
“…The low absorption of some fractions may be partly explained by the instability of the compounds during the digestive process. Green et al 32 demonstrated using an in vitro model that 80% of catechins are destroyed during the process of digestion. Studies of anthocyanin pharmacokinetics in humans 33 from either wine or grape juice showed similar T max (0.5-1.5 hours) to fractions IV and V but had a lower serum percentage dose=mL at C max .…”
Section: Discussionmentioning
confidence: 99%
“…4 HPLC chromatograms of organic acid concentrations in the apical chamber before (t 0 min) and after (t 120 min) the cell monolayer transport bioassay as well as the organic acid concentrations in the basolateral chamber at t 120 min; from banana (a) and sweet potato (b) Eur J Nutr (2011) 50: 31-40 37 studied in vitro. Many other nutrients such as carotenoids [26], iron [27,28], calcium [29,30] or polyphenols [27,31] have been studied for their intestinal bioavailability using a model of in vitro digestion alone or combining in vitro digestion/Caco-2 cell. However, in most of these studies, the digests were directly used for intestinal absorption without focusing on the nutrient release as a function of time per se.…”
Section: In Vitro Digestion and Release Of Organic Acidsmentioning
confidence: 99%
“…[10]. The poor oral bioavailability of catechins, mainly EGC and EGCG, is attributed to their poor stability, as shown in studies of in vitro digestive simulated gastro-intestinal tract (GIT) conditions [11], and to poor intestinal permeability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of bovine, soy, rice milk, ascorbic acid and citrus juice resulted in the increase of post-digestion recovery of EGCG, EGC, ECG and EC [11]. Hence, protecting the catechins from the GIT environment will increase their post-digestion recovery for oral delivery purposes.…”
Section: Introductionmentioning
confidence: 99%